(untitled) (Vietnam Journal of Community Medicine, 2023)
Objectives: Description of the need for maternal care after cesarean section at the National Hospital of Obstetrics and Gynecology in 2022- 2023. Method: The cross-sectional descriptive study design, prospective study, combining quantitative and qualitative research on 385 women who had a cesarean section on August 1, 2022, and midwives and nurses working at the National Hospital of Obstetrics and Gynecology. Use pre-designed questionnaires for interviewing and visiting pregnant women. Organize group discussions with nurses and midwives. Results: There are 91.4%; 46.5% of pregnant women want to have family members; health care workers after cesarean. The percentage of pregnant women wishing to have two caregivers is the highest (82.1%). Therefore, 83.1% of pregnant women require the post-operative service room. The need for post-operative care support of pregnant women is very high, with which child care and monitoring accounts for the highest rate of 65.2%; breastfeeding is 57.9%; exercise and rehabilitation accounted for 43.6% and personal hygiene accounted for 45.2%. The percentage of pregnant women who want postoperative care services is high, such as incision plasma projection (93.5%), breast massage (79.7%) and perineal steaming (28.6%). There are 90.1% and 77.9% of women, respectively, who want the services of umbilical cord plasma projection and neonatal massage after surgery. Conclusion: The need for care of pregnant women after cesarean section is increasing, including the need for respect for the mother and the newborn.